2010
DOI: 10.1007/s10806-010-9293-z
|View full text |Cite
|
Sign up to set email alerts
|

Farmers Engaged in Deliberative Practices; An Ethnographic Exploration of the Mosaic of Concerns in Livestock Agriculture

Abstract: A plethora of ethical issues in livestock agriculture has emerged to public attention in recent decades, of which environmental and animal welfare concerns are but two, albeit prominent, themes. For livestock agriculture to be considered sustainable, somehow these interconnected themes need to be addressed. Ethical debate on these issues has been extensive, but mostly started from and focused on single issues. The views of farmers in these debates have been largely absent, or merely figured as interests, inste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…Per entity, i.e., animals, humans (animal keepers and consumers) and environment, categories with aspects relevant for attitudes toward pig husbandry are presented. Sources Barnett et al 2001;Beekman et al 2002;Boogaard et al 2011a, b;Cohen et al 2009Cohen et al , 2012Driessen 2012;Fraser 1999;Frederiksen et al 2010;Harper and Henson 2001;Huber-Eicher and Spring 2008;Kanis et al 2003;Krystallis et al 2009;Lagerkvist et al 2006;Marchant-Forde 2009;McGlone 2001;Mepham 2000;Meuwissen and van der Lans 2005;Michalopoulos et al 2008;Millman 2011;Ngapo et al 2003;Petit and van der Werf 2003;Te Velde et al 2002;Tuyttens et al 2010;Vanhonacker et al 2010Vanhonacker et al , 2008Verdoes and Swinkels 2003;Von Essen and McCurdy 1998;Webster 2001 Attitudes of different stakeholders toward pig husbandry: A study to determine conflicting… 397 necessary and 5: maximal AC necessary); levels 1 and 2 became level 1, levels 3 and 4 became level 2, levels 5 and 6 became level 3, levels 7 and 8 became level 4 and levels 9 and 10 became level 5). The scale decrease was done to maximize scale variation.…”
Section: Discussionmentioning
confidence: 99%
“…Per entity, i.e., animals, humans (animal keepers and consumers) and environment, categories with aspects relevant for attitudes toward pig husbandry are presented. Sources Barnett et al 2001;Beekman et al 2002;Boogaard et al 2011a, b;Cohen et al 2009Cohen et al , 2012Driessen 2012;Fraser 1999;Frederiksen et al 2010;Harper and Henson 2001;Huber-Eicher and Spring 2008;Kanis et al 2003;Krystallis et al 2009;Lagerkvist et al 2006;Marchant-Forde 2009;McGlone 2001;Mepham 2000;Meuwissen and van der Lans 2005;Michalopoulos et al 2008;Millman 2011;Ngapo et al 2003;Petit and van der Werf 2003;Te Velde et al 2002;Tuyttens et al 2010;Vanhonacker et al 2010Vanhonacker et al , 2008Verdoes and Swinkels 2003;Von Essen and McCurdy 1998;Webster 2001 Attitudes of different stakeholders toward pig husbandry: A study to determine conflicting… 397 necessary and 5: maximal AC necessary); levels 1 and 2 became level 1, levels 3 and 4 became level 2, levels 5 and 6 became level 3, levels 7 and 8 became level 4 and levels 9 and 10 became level 5). The scale decrease was done to maximize scale variation.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, citizens who oppose certain practices can provide their political support to new regulations. Both approaches remove control from the producer, perhaps explaining why the dairy industry has tended to either avoid interacting with the public on contentious issues (perhaps hoping that the issue will pass) or has relied on an expert-knows-best mentality, focused on disseminating information to educate the public on industry perspectives to these practices (Driessen, 2012). Consumer attitude surveys indicate that food safety is the highest priority when deciding what to purchase (Vanhonacker et al, 2010;Ingenbleek and Immink 2011).…”
Section: The Consumer and The Citizenmentioning
confidence: 99%
“…This naturalness plays a role in the assessment of animal welfare (Mepham 2000, Tuyttens 2010, Vanhonacker et al 2008, 2012 Essence meat Meat is seen as a part of humans' diet (Aarts 2001). The importance of pig meat plays a role in the evaluation of pig husbandry Justice Animal: value The value of an animal will have an influence on how much justification an animal needs (Asseldonk et al 2005).…”
Section: Data Collectionmentioning
confidence: 99%
“…The importance of pig meat plays a role in the evaluation of pig husbandry Justice Animal: value The value of an animal will have an influence on how much justification an animal needs (Asseldonk et al 2005). In the evaluation of animal production systems, justice in relation to animal value is of importance (Mepham 2000) Human: fair-trade Justice on fair-trade is important in the ethical debate about animal production systems (Driessen 2012, Mepham 2000 and food concerns (Michalopoulos et al 2008). In earlier research it is found that concerns exist about fair-trade (Driessen 2012) Human: financial costs Justice on financial costs (affordable food) is important in the ethical debate (Mepham 2000).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation